Adjustment among first year students in a Malaysian university. - Jusoh, Rosnani; Abdullah, Maria Chong; Elias, Habibah; Mahyuddin, Rahil; Uli, Jegak (2008)
Based on the adjustment model by Baker and Siryk (1984), this study aimed to explore college adjustment processes experienced by 250 first year university students attending various undergraduate programs at a Malaysian public university. In addition it examined the role of gender in college adjustment and the impact of college adjustment on students academic achievement. The study employed a correlation design and data was analyzed using descriptive and inferential statistics to address the research objectives. Findings from this study showed that students overall adjustment was at a moderate level and male students were found to be better adjusted compared to female students. Results indicated that over a period of one semester students academic achievement was found to be significantly predicted by college overall adjustment, academic adjustment and personal-emotional adjustment.